A case study of consequences analysis of ammonia transportation by rail from Gurun to Port Klang in Malaysia using Safti computer model - Che Hassan, Che Rosmani; Puvaneswaran, B.; Abdul Raman, Abdul Aziz; Mahmood, Noor Zalina; Hung, F.C.; Sulaiman, N.M.; Puvaneswaran, A.; Balasubramaniam, L. (2009)
There are many ways of describing the quantitative risk assessment (QRA) methodology, but in general, the basic steps include: System Definition, Hazard Identification, Frequency Analysis, Consequence Modeling, and Risk Calculations and Assessment. The present study is aimed at the Consequence Analysis, which was an integral part in the QRA for the transportation of ammonia by rail from Gurun to Port Klang. The software package SAFETI has been used to model the resulting behavior of the released ammonia and the extent of the damage expressed in terms of distance to certain effect levels. Besides, sensitivity analysis was also carried out to identify the impacts of atmospheric conditions on ammonia gas dispersions. The results indicated an increase in the ammonia gas dispersion distances for releases at higher atmospheric temperatures of lower atmospheric humidity (e.g. for rupture case with wind speed 3m/s, at 15oC, the dispersion distance was 835.4 m, while at 35oC, it increases to 866.2 m). However, further analysis of the effects atmospheric humidity on the ammonia gas dispersions was required to determine the differences in the trend for the 25 mm and 100 mm leak cases compared to the rupture case.